Karakteristik Ketimpangan Provinsi Banten: Pendekatan Struktur Ekonomi, Indeks Entropi Thiell, dan Multidimensional Scaling - Syaifudin, Rizal; Mangara, Togi Haidat; Desmawan, Deris; Julliansyah, Muhammad Raihan; Putri, Cantika Sindy Aliya; Mahintan, Loanna Zahra (Forum Kerjasama Pendidikan Tinggi, 2024)
The increase of the economy in one region can be considered as two things. In one hand, it also encourages the increase of its society welfare but on the other hand, the concentration of economic activities in particular economic sector or region can potentially lead to the inequality of development in the larger regions. This research aims to analyze whether there is an inequality in regencies/municipalities in Banten Province. To achieve this goal, the analysis is conducted in two steps. The first one is to analyze the economic structure of all regencies/municipalities in Banten Province and then the result of that analysis is used to identify the inequality by using Intra Theill Entropy Index. From those analyses, it is found that the developing economic sector in Banten Province is mainly dominated by modern economic sectors, for example Manufacturing. Furthermore, it is also found that there is a big gap regarding the inequality in Banten Province measured by the high Intra Theill Entropy Index which is marked by the high economic concentration in Cilegon City, Tangerang City, and Serang City.